Periconception maternal low-protein diet adversely affects male mouse fetal bone growth and mineral density quality in late gestation. (5th June 2021) - Lanham, Stuart A.; Smith, Stephanie J.; Watkins, Adam J.; Lucas, Emma S.; MacCaoilte, Niamh; Oreffo, Richard O.C.; Fleming, Tom P.; Eckert, Judith J.
Abstract: Adverse programming of adult non-communicable disease can be induced by poor maternal nutrition during pregnancy and the periconception period has been identified as a vulnerable period. In the current study, we used a mouse maternal low-protein diet fed either for the duration of pregnancy (LPD) or exclusively during the preimplantation period (Emb-LPD) with control nutrition provided thereafter and postnatally to investigate effects on fetal bone development and quality. This model has been shown previously to induce cardiometabolic and neurological disease phenotypes in offspring. Micro 3D computed tomography examination at fetal stages Embryonic day E14.5 and E17.4, reflecting early and late stages of bone formation, demonstrated LPD treatment caused increased bone formation of relative high mineral density quality in males, but not females, at E14.5, disproportionate to fetal growth, with bone quality maintained at E17.5. In contrast, Emb-LPD caused a late increase in male fetal bone growth, proportionate to fetal growth, at E17.5, affecting central and peripheral skeleton and of reduced mineral density quality relative to controls. These altered dynamics in bone growth coincide with increased placental efficiency indicating compensatory responses to dietary treatments. Overall, our data show fetal bone formation and mineral quality is dependent upon maternal nutritional protein content and is sex-specific. In particular, we find the duration and timing of poor maternal diet to be critical in the outcomes with periconceptional protein restriction leading to male offspring with increased bone growth but of poor mineral density, thereby susceptible to later disease risk.